Comparative Efficiency of Guar (Oy Amopsis Tetragoyoloba (Linn. Taub.) Varieties With Varying Phosphorus Levels & Seed Rates - Tomer, P S; Dalal, S K; Gill, P S; Bishnoi, K C (Annals of Arid Zone, 2016)
The experiment was conducted on two Guar varieties (No.2 and F.S. 277) under four levels of phosphorus (0,40,80 and 120Kg P2O5/ha) and three seed rates (40, 55 &, 70 Kg seed/ha) at Haryana Agricultural University, Hissar. On an average both the varieties were at par in terms of growth and forage production. Maximum forage yield was obtained when F.S. 277 variety was sown with 55 Kg seed/ha or variety ,No. 2 sown with 40 Kg seed/ha. Among phosphorus levels, 40 Kg P205/ha increased the forage yield significantly over control. There was no substantial increase in forage yield beyond 40 Kg P205/ha.